2022
DOI: 10.1101/2022.01.03.21268111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The hyper-transmissible SARS-CoV-2 Omicron variant exhibits significant antigenic change, vaccine escape and a switch in cell entry mechanism

Abstract: Vaccination-based exposure to spike protein derived from early SARS-CoV-2 sequences is the key public health strategy against COVID-19. Successive waves of SARS-CoV-2 infections have been characterised by the evolution of highly mutated variants that are more transmissible and that partially evade the adaptive immune response. Omicron is the fifth of these Variants of Concern (VOCs) and is characterised by a step change in transmission capability, suggesting significant antigenic and biological change. It is c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
229
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(254 citation statements)
references
References 77 publications
23
229
1
1
Order By: Relevance
“…5a). These ndings suggests Omicron spike preferentially enter through ACE2-mediated endocytosis and this is in support with recent studies which showed Omicron preferentially enters cells by endocytic pathway 29,51 . In contrast, highly virulent variants like Delta could use both a) endocytic pathway and activation of S1/S2 protein mediated by Cathepsin B/L proteases and b) cell surface entry by activation of S1/S2 using serine protease TMPRSS2.…”
Section: Discussionsupporting
confidence: 92%
“…5a). These ndings suggests Omicron spike preferentially enter through ACE2-mediated endocytosis and this is in support with recent studies which showed Omicron preferentially enters cells by endocytic pathway 29,51 . In contrast, highly virulent variants like Delta could use both a) endocytic pathway and activation of S1/S2 protein mediated by Cathepsin B/L proteases and b) cell surface entry by activation of S1/S2 using serine protease TMPRSS2.…”
Section: Discussionsupporting
confidence: 92%
“…While there is emerging biological evidence of possible lower virulence of Omicron compared to previous variants due to modified cell entry mechanisms and preferential replication in bronchi rather than the lung parenchyma (6, 7, 14, 15), even a virus resulting in similar or lower clinical severity to earlier variants could overwhelm health services if protection conferred by prior COVID-19 infection and/or SARS-CoV-2 vaccination against severe disease is reduced. While there are now several reports from South Africa and other countries of reduced risk of severe disease in the fourth wave and in patients infected with Omicron compared to Delta (16-21) in the context of a high seroprevalence setting such as South Africa, with moderate SARS-CoV-2 vaccination coverage (39% and 46% of adults fully vaccinated in South Africa and the Western Cape respectively by end December 2021) (22), it is important to establish whether protection against severe disease conferred by prior infection and/or vaccination is maintained against Omicron.…”
Section: Introductionmentioning
confidence: 99%
“…This fitness advantage has been tentatively linked with a substantial ability to evade immunity from previous infection ( Pulliam et al, 2021 ), which might be consistent with the high number of non-synonymous mutations and indels observed in the S gene compared with the reference SARS-CoV-2 genome. These include a number of previously described RBD mutations associated with the aforementioned VOC, such as T478K and N501Y, plus E484A, which suggested significant immune evasion properties, later confirmed by a number of in vitro studies ( Cele et al, 2021 ; Garcia-Beltran et al, 2021 ; Schmidt et al, 2021 ; Willett et al, 2022 ). Based on early epidemiological data and on the growing number of imported cases reported abroad, on December 1 st , 2021 WHO included B.1.1.529 in the list of VOCs under the “omicron” designation.…”
Section: Introductionmentioning
confidence: 72%
“…This unusual pattern of mutations results in significant immune escape in vitro and in an enhanced reinfection potential in vivo ( Cele et al, 2021 ; Garcia-Beltran et al, 2021 ; Schmidt et al, 2021 ; Willett et al, 2022 ). Moreover, omicron displays an altered cellular tropism and cell entry mechanism, which depends on the acquisition of an enhanced ability to rely on the TMPRSS2-independent endosomal route ( Peacock et al, 2022 ; Willett et al, 2022 ). It is presently unclear whether and to which extent the XLI insertion provides a contribution to the unique biological properties of this variant.…”
Section: Resultsmentioning
confidence: 99%